Cardiac Oxidative Status in CCl 4 -Exposed Rats Treated with Extracts of Dialium guineense Stem Bark (Global Journal of Science Frontier Research, 2023)
The present study investigated cardiac oxidative status in carbon tetrachloride (CCl 4 )exposed rats treated with aqueous and ethanol extracts of Dialium guineense stem bark. Adult male Wistar rats (n = 25) weighing 170 -190 g (mean weight = 180 ± 10 g) were randomly assigned to five groups (5 rats per group): normal control, CCl 4 control, silymarin, aqueous extract and ethanol extract groups. With the exception of normal control, the rats were exposed to CCl 4 at a single oral dose of 1.0 mL/kg body weight, bwt. Rats in the silymarin group were administered silymarin (standard cardioprotective drug) at a dose of 100 mg/kg bwt, while those in the two treatment groups received 1000 mg/kg bwt of aqueous or ethanol extract orally for 28 days. Activities of antioxidant enzymes such as catalase, superoxide dismutase (SOD), glutathione peroxidase (GPx) and glutathione reductase (GR) were evaluated in heart homogenate.
Keywords: cardioprotection; dialium guineense; heart; lipid peroxidation; oxidative stress